Strategy of Extension Industrial Business and Evaluation of their Alternatives - Kiselis, Algirdas Antanas (Ekonomika, 2002)
This article is appointed to analyse actual problems of transformation contemporary Lithuanian economic system into market economic conditions. In the process economical extension important domain is assurance of growing vitality industrial business. There is taken an information model enabling relate demand and supply of industrial production as market equilibrium model.In the environment of industrial business exists complicated definite and probability quality economical dependence relations. Constantly changing process in the market provides alterations of industrial business also in the most accordance with alterations of market.There are given the economical system model in this article. Also there are given systematic researches and analysis of the meanings of industrial business economical indicators, regulation of system in accordance with determinate influence to the economical system of industrial business. The model of system is appointed for creating a suitable management strategy of industrial business and aspiration the. goal of economical system. There are performed analysis of systematic solutions and evaluating of alternative system solutions for using in business.